ON THE QUESTION OF THE ESSENCE AND CLASSIFICATION INTERACTIVE TECHNOLOGIES - V.V. Revenko (Academy of Cognitive and Natural Sciences, 2008)
The article is devoted to the essence of interactive learning, the notions "interactive learning", "interactive methods", "interactiveforms of learning" and "interactive technologies" are differentiated. The classification o f interactive technologies, which has been worked out by the author, is presented.